More Than “Push” and “Pull”? Plant-Soil Feedbacks of Maize Companion Cropping Increase Chemical Plant Defenses Against Herbivores - Mutyambai, Daniel M.; Bass, Ethan; Luttermoser, Tim; Poveda, Katja; Midega, Charles A. O.; Khan, Zeyaur R.; Kessler, André (Frontiers in Ecology and Evolution, 2019)
Plants can alter nutritional availability, structure, and chemistry of the soil they grow in. These soil changes can positively or negatively influence the growth and metabolism of other plants that co-occur or grow later in the conditioned soil. Plant-soil feedbacks could affect community interactions and dynamics but also be applied in sustainable agriculture to promote plant growth and resistance to pests. In this study, we use a maize companion cropping system, commonly known as “push-pull”, as a model to investigate soil-mediated effects of functional biodiversity, on maize plant growth and resistance against insect herbivores. We grew maize in soils collected from push-pull (polyculture) and non-push-pull (monoculture) fields. We evaluated maize performance by measuring plant growth, as well as resistance traits (herbivore oviposition and larval feeding, production of defense-related volatile and non-volatile secondary defense metabolites). Maize plants grown in soil conditioned by push-pull companion cropping had a higher growth rate compared to those grown in soil from non-push-pull monoculture fields. In addition, soil from push-pull fields induced a constitutively higher and qualitatively different emission of volatile organic compounds than soil from non-push-pull fields. Moreover, secondary defense metabolites such as 2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one (DIMBOA), were produced in larger quantities in plants grown in soil from push-pull fields compared to those from monoculture fields. These soil-mediated alterations in plant secondary metabolism were associated with reduced herbivory by larvae of the stemboring pest Chilo partelllus. This study provides novel evidence that plant-soil feedbacks can affect plant metabolism, growth, and resistance to pests. The observed soil-mediated effects on maize plant secondary metabolism can be viewed as emergent properties of plant community composition as well as a potent mechanism of associational resistance. In addition, these soil-conditioning effects provide a novel pest control mechanism of push-pull companion cropping.